2021
DOI: 10.9770/jesi.2021.8.3(42)
|View full text |Cite
|
Sign up to set email alerts
|

How we can benefit from personal finance management applications during the COVID-19 pandemic? The Polish case

Abstract: The aim of this article is to determine if and to what extent sociodemographic factors are related to how home budget management applications are evaluated. The authors attempted to verify to what extent applications supporting personal finance management are beneficial and popular in Poland via a CAWI online survey. The architecture of the research covered the following areas: the name of the application used, its method of use, the level of complexity of the software installation process, evaluation of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
4
1
2
Order By: Relevance
“…In addition, the European Central Bank reported that the workforce shrank by about 5 million in the first half of 2020 [80], that companies are closing or going bankrupt in many countries, and that the severe stock market downturn has reduced savings and pension investments. The current economic situation related to the COVID-19 pandemic forces consumers to use remote channels to access their finances [81]. Increasing uncertainty, reduced income, or a complete loss of livelihoods may lead to the financial ruin of households.…”
Section: Investors' Attitudes Toward Esg Investing and Financial Well...mentioning
confidence: 99%
“…In addition, the European Central Bank reported that the workforce shrank by about 5 million in the first half of 2020 [80], that companies are closing or going bankrupt in many countries, and that the severe stock market downturn has reduced savings and pension investments. The current economic situation related to the COVID-19 pandemic forces consumers to use remote channels to access their finances [81]. Increasing uncertainty, reduced income, or a complete loss of livelihoods may lead to the financial ruin of households.…”
Section: Investors' Attitudes Toward Esg Investing and Financial Well...mentioning
confidence: 99%
“…Zapotrzebowanie na usługi planowania finansowego gwałtownie wzrasta w miarę jak rynek finansowy staje się coraz bardziej złożony, a ludzie stają się bardziej świadomi znaczenia wykwalifikowanego doradztwa finansowego. Również okres pandemiczny COVID-19 wpłynął na przyspieszenie cyfryzacji w obszarze finansów (Waliszewski i Warchlewska, 2022, 2021d. Zastosowanie nowoczesnych rozwiązań finansowych służy nie tylko minimalizowaniu kosztów związanych z zatrudnianiem, ale również ukierunkowaniu działań w celu próby rozwiązania problemów, z którymi borykają się klienci.…”
Section: Idea Nowoczesnych Rozwiązań Finansowychunclassified
“…oceny jakości aplikacji PFM wśród młodego pokolenia oraz (2) badanie nt. wykorzystania aplikacji PFM -badanie ogólnopolskie , 2021a, 2021b. Ponadto przedstawiono wyniki badań wtórnych w zakresie wpływu edukacji finansowej na postawy konsumentów wobec finansów.…”
Section: Edukacja Finansowa a Nowoczesne Technologieanaliza Teoretycz...unclassified